EFEKTIVITAS KERJASAMA PENANGGULANGAN PEREDARAN NARKOBA ILEGAL (MERIDA INITIATIVE) ANTARA PEMERINTAH MEKSIKO DAN AMERIKA SERIKAT (2007-2012) - Samosir, Efragil; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study is focused on the effectiveness of the cooperation of eradicate illegal drugstrafficking (Merida Initiative) between the United States and Mexico in 2006-2012. Theactivity of Drugs Trans Organizations (DTOs) in the U.S. and Mexico have caused negativeimpacts on both countries. Mexico's DTOs are major supplier of cocaine, heroin,methamphetamine, and marijuana into U.S. territory. The competition between DTOs in therace for the distribution area in Mexico has caused thousands of deaths each year. Thiscommon problem eventually became cooperation between U.S. and Mexican governments,which is called Merida Initiative.This study uses a qualitative research method that uses books, journals and competentwebsites to explain the effectiveness of the Merida Initiative cooperation beetwen U.S. andMexico in 2006-2012. The writer uses the theory of cooperation by KJ Holsty andneoliberal’s perspective. The writer also uses nation state as the level of analysis.This study found that the Merida Initiative cooperation of U.S. and Mexico in 2006-2012 is not operating effectively. The benefits of this cooperation is only perceived by theMexican government. Through Merida Initiative programs, there is a very significantimprovement in the judicial system and law enforcement in Mexico. As for the U.S.government who has provided assistance over U.S. $ 2 billion during the year of 2006-2012,the Merida Initiative programs have failed to reduce consumption and demand for drugs inthe United States.Keywords: Drugs Trans Organization (DTO), cooperation, effectiveness.